2021
DOI: 10.1158/1535-7163.mct-20-0831
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Small-molecule BRD4 Degrader CFT-2718 in Small-cell Lung Cancer and Pancreatic Cancer Models

Abstract: Targeted, catalytic degradation of oncoproteins using heterobifunctional small molecules is an attractive modality, particularly for hematological malignancies which are often initiated by aberrant transcription factors and are challenging to drug with inhibitors. BRD4, a member of the Bromodomain and Extraterminal (BET) family, is a core transcriptional and epigenetic regulator that recruits the P-TEFb complex, which includes Cdk9 and cyclin T, to RNA polymerase II (pol II). Together, BRD4 and CDK9 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…This is supported by a recent study in which a new BRD4‐targeting degrader was identified to selectively increase the expression of cleaved Poly (ADP‐ribose) polymerase‐1 (PARP) and apoptosis in treatment‐refractory solid lung cancer. [ 36 ] It was also demonstrated that BET degraders such as ZBC260 and dBET can effectively induce Bim‐dependent apoptosisof human lung cancer cells via the suppression of Mcl‐1 and c‐FLIP. [ 18 ] Thus, it will be interesting to further explore the underlying mechanism of CREATE in controlling cancer cells and TAMs apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent study in which a new BRD4‐targeting degrader was identified to selectively increase the expression of cleaved Poly (ADP‐ribose) polymerase‐1 (PARP) and apoptosis in treatment‐refractory solid lung cancer. [ 36 ] It was also demonstrated that BET degraders such as ZBC260 and dBET can effectively induce Bim‐dependent apoptosisof human lung cancer cells via the suppression of Mcl‐1 and c‐FLIP. [ 18 ] Thus, it will be interesting to further explore the underlying mechanism of CREATE in controlling cancer cells and TAMs apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The novel BRD4-targeting agent CFT-2718 showed potent antitumor activity in xenograft mice. The intensity and duration of apoptosis induction and tumor proliferation inhibition by CFT-2718 surpassed that of the CDK kinase inhibitor dinaciclib in SCLC cells (Sun et al, 2021). OTX015 showed significant anti-cancer activity in NSCLC cells with or without EML4-ALK translocation and EGFR, KRAS mutations (Riveiro et al, 2016).…”
Section: Betimentioning
confidence: 95%
“… 48 , 49 , 50 CFT-2718 JQ-1 analog CRBN ligand BRD4 SCLC In vitro ; In vivo SCLC PDX Zong et al.48, Sun et al. 51 QCA570 QCA276 CRBN ligand BRD2, BRD3, BRD4 LUAD; LSCC In vitro ; In vivo HCC827/AR xenograft Qin et al. 52 ; Liu et al.…”
Section: Progress In the Protac Development For Lung Cancer Treatmentmentioning
confidence: 99%
“… 46 Multiple BRD4 or pan-BRD PROTACs have been developed that showed promising antitumor efficacy in the xenograft tumors from EGFRi-resistant cell lines and lung cancer PDXs. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 The protein tyrosine phosphatase SHP2 is frequently activated in lung cancer to maintain a fully activating oncogenic signaling and thus serves as an attractive therapeutic target. A potent SHP2 PROTAC, D26, was developed 54 and shown to have therapeutic efficacy alone, or in combination with the third-generation EGFR inhibitor, osimertinib, in blocking osimertinib-resistant lung cancer cells.…”
Section: Progress In the Protac Development For Lung Cancer Treatmentmentioning
confidence: 99%